EFEKTIVITAS RELAKSASI BENSON TERHADAP PENURUNAN NYERI PADA IBU POSTPARTUMSECTIO CAESAREA - Anita ' Yusliana; Misrawati ' '; Safri ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Surgery that causes severe pain physiological response as compared to a normal delivery was called sectio caesarea.The alternative to reduce pain with benson relaxation. Benson relaxation was the developed of relaxation response method by involving patient is belief factor. This research was aimed to explore the effectiveness of benson relaxation for reduction pain in postpartum mothers sectio caesarea. The method used this research was quasi experimental with pre test and post test design with control group. The instruments used numeric rating scale to measure pain intensity. The sampling technique used purposive sampling where the quantity of research sample was 30 respondents which are divided into 2 groups, namely intervention group and control group. Benson relaxation carried out for 15 minutes each day for 2 days. The univariate analysis was conducted to show pain distribution and bivariate analysis was conducted by Dependent sample T-test and Independent sample T test. The result show that after benson relaxation was applied towards intervered group, it was obtained that mean of respondents category pain was reducing at 2,86 (low pain) with the reduction was 1,53 and mean of postpartum mother sectio caesarea pain without given benson relaxation in control group was 3,76 (modarate pain) with the reduction was 0,30. The statistic showed up p value (0,000)< 0,05 which mean that benson relaxation effective to reduce pain of postpartum mothers sectio caesarea. Based on the result, benson relaxation can be recomended as nursing intervention of postpartum mother sectio caesarea. Keywords: Benson relaxation, pain, sectio caesarea